2022
DOI: 10.1002/chem.202202080
|View full text |Cite
|
Sign up to set email alerts
|

Cover Feature: Azole‐Directed Cobalt‐Catalyzed Asymmetric Hydrogenation of Alkenes (Chem. Eur. J. 44/2022)

Abstract: With his hand holding the sail and his feet on the sailboard, the position of the windsurfer mimics the key strategy of this work: the activation of hydrogenated substrates by chelating coordination with cobalt. The surfer is the cobalt catalyst holding the sail to coordinate parazole, and with his foot on the hydrogenated substrate board to coordinate the vinyl group. Bubbles in the seawater represent the main reagent of the reaction, hydrogen, the dolphin represents the hydrogenated product of this reaction,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In 2022, Zhang et al reported the azole-directed Co-catalyzed asymmetric hydrogenation of alkenes with high yields and ee values on 46 examples (Scheme 3c). 23 In subsequent studies, the asymmetric hydrogenation of more and more complex substrates was realized from disubstituted olefins to tetrasubstituted olefins. In 2020, Zhang et al described Co-catalyzed asymmetric hydrogenation of a,bunsaturated carboxylic acids.…”
Section: Hydrogenationmentioning
confidence: 99%
“…In 2022, Zhang et al reported the azole-directed Co-catalyzed asymmetric hydrogenation of alkenes with high yields and ee values on 46 examples (Scheme 3c). 23 In subsequent studies, the asymmetric hydrogenation of more and more complex substrates was realized from disubstituted olefins to tetrasubstituted olefins. In 2020, Zhang et al described Co-catalyzed asymmetric hydrogenation of a,bunsaturated carboxylic acids.…”
Section: Hydrogenationmentioning
confidence: 99%
“…Azole-Directed Cobalt/BPE-Catalyzed Asymmetric Hydrogenation of Alkenes. [70] Scheme 33. AH of vinyl silanes.…”
Section: C=o Hydrogenationmentioning
confidence: 99%
“…[69] W. Zhang and co-workers reported the synthesis of enantioenriched pyrazole compounds via the AH of prochiral azole-functionalized alkenes. [70] After careful screening of different chiral ligands, CoCl 2 / Me DuPhos and CoCl 2 / Ph BPE resulted in the highest conversion and up to 98 % ee in MeOH using Zn as additive. Similar activity and selectivity were observed in other alcoholic solvents such as EtOH, iPrOH, tBuOH.…”
Section: Functionalized Acyclic Olefinsmentioning
confidence: 99%
“…After the discovery of cobalt catalyzed asymmetric hydrogenation of functionalized olefins 33 via high throughput screening, first row transition metals 34 in asymmetric hydrogenation 35 have become an attractive and important area of research, especially Co-catalyzed enantioselective olefin hydrogenation. The use of readily available cobalt precursors and enantiopure ligands have generated highly active catalysts for the synthesis of levetiracetam, 36 hydrogenation of N-functionalized imines, 37 α,β-unsaturated carboxylic acids, [38][39][40] E/Z alkenes, 41 functionalized alkynes, 42,43 enynes, 44 minimally functionalized alkenes, [45][46][47][48] azole derived tri-substituted alkene, 49 and other unsaturated compounds. 13,34,[50][51][52][53] A handful of Rh-based homogeneous catalysts are known for the preparation of chiral N-(indan-1yl)-acetamide (1b) [54][55][56][57] or, 1-indanamine (1c).…”
Section: Introductionmentioning
confidence: 99%